Clearing in the View of Islamic Economic law - Ahmad Muqorobin; Yunita Wulandari (Universitas Darusssalam Gontor, 2017)
The financial flow can be regarded good or bad based on the function of centralbank in managing the circulation of money in Indonesia. Currently, the transanctiongiral money is more dominant than cartel money in the society. Because it tends to bemore effective, effecient and easy used in all economic activities. Most of the paymentsmaking up the transactions flow between several banks, which need one of the instrumentsthat settles the flow money circulated among the banks known as clearing. The objectiveof research is to know the mechanism of clearing and the structure of ‘aqd in the bankfrom Islamic law perspective. The finding shows that the application of clearing inIslamic banking has used Aplikasi kliring the contract of waka>lah, specifically waka>lahbilujroh that the bank will get the fees to represent the customers settling the payment.